A Study on Dementia Knowledge, Burden from Behavioral and Psychological Symptoms of Dementia, Attitude toward Dementia in Certified Caregivers - Park, A Young; Park, A Young; Park, Eun Hee; Park, Hae-Ryoung (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study was to identify the relationships among dementia knowledge, burden from Behavioral and Psychological Symptoms of Dementia (BPSD), attitudes toward to dementia of 127 certified caregivers. Methods/Statistical analysis: This is descriptive correlation research aimed at investigating knowledge about dementia, the burden from behavioral and psychological symptoms of dementia (BPSD), and attitudes toward dementia in certified caregivers, who had received special training related to dementia. To grasp the knowledge on dementia, burden with behavioral and psychological symptoms of dementia, and attitude towards dementia according to the subjects’ general characteristics, the t-test and ANOVA were used, and Scheffe’ test was conducted for post-hoc verification. Findings: The differences in dementia knowledge, the burden from behavioral and psychological symptoms of dementia (BPSD), and attitudes toward dementia by the general characteristics are as follows: Knowledge differed significantly by age (F=6.145, p =.003), education (F=7.843, p〈.001). Attitudes differed significantly by education (F=3.191, p =.045), education experiences about dementia (F=4.350, p〈.001). The mean score of dementia knowledge was 20.04±3.78 out of 30, and the means of burden from behavioral and psychological symptoms of dementia (BPSD) was 61.37±12.81 out of 100 and the means of dementia attitudes was 95.24±13.24 out of 140. Attitudes toward dementia in caregivers differed significantly depending on their level of education, education experience about dementia. No difference was found in the burden with Behavioral and Psychological Symptoms of Dementia (BPSD) by the general characteristics. The degree of attitudes differed significantly by education (F=3.191, p=.045) and experience of dementia education (t=4.350, p〈 .001) Attitudes also had a significantly correlated with BPSD(r = -2.16, p =-0.15) and dementia knowledge(r = .197, p =.027). Improvements/Applications: The results suggest that it is necessary to provide continuous education and support to improve dementia knowledge and reduce burden from behavioral and psychological symptoms of dementia (BPSD) of certified caregivers in order to improve attitudes of dementia.